MENAKAR PROFESIONALISME GURU: ANTARA BEBAN KERJA DAN KINERJA PENDIDIKAN - Muttaqin, Aziz Iwan; Yeni Rahmawati; Erna Yayuk (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Teacher professionalism is one of the key factors in determining the quality of education. Teachers do not merely serve as conveyors of instructional content, but also as educators who shape students’ character and competencies. In practice, teacher professionalism is often associated with a teacher’s ability to perform duties effectively and demonstrate optimal performance. However, the reality on the ground shows that various factors such as workload, work environment, professional competence, and institutional support also influence teachers’ performance in carrying out their duties. This article aims to conduct a conceptual review of teacher performance within the context of educational professionalism, focusing on three main aspects: the definition of performance, factors influencing teacher performance, and indicators of teacher performance in educational practice. The method used in this study is a literature review, examining various relevant literature on teacher professionalism and educational performance. The study findings indicate that teacher performance is a manifestation of teachers’ professional ability to effectively plan, implement, and evaluate the learning process. Teacher performance is influenced by various factors, both internal and external, such as competence, motivation, school leadership, organizational culture, as well as the reward system and workload. Furthermore, indicators of teacher performance can be observed through aspects of instructional planning, instructional delivery, assessment of learning outcomes, and continuous professional development. By understanding these factors, it is hoped that efforts to enhance teacher professionalism can be carried out in a more systematic and sustainable manner, thereby improving the overall quality of education.